The determinants of green banking adaptation in Bangladesh: The City Bank Limited banking perspective - Jilany, Fardin Ahmed (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.